2005
DOI: 10.1097/01.ju.0000173075.62504.73
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Technique Using Bipolar Energy in Transurethral Prostate Surgery: A Prospective, Randomized Comparison

Abstract: : Transurethral surgery with PlasmaKinetic bipolar energy seems to be a promising alternative to prostatic tissue removal with shorter operative, catheterization and hospitalization times, although increased rates of postoperative irritative symptoms and urethral stricture formation must be further evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
109
3
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 17 publications
15
109
3
9
Order By: Relevance
“…Yang et al 9 found a significant advantage with the bipolar method, but no significant difference for bleeding tendency was shown in recent studies or in our patients. 10,23 An increased risk of stricture after bipolar resection 20,21 was not confirmed by our findings, which is in accordance with other authors. 8,10,14 The higher number of strictures in the 'bipolar' study arm of some authors 10 might be because of the TUR in saline system.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Yang et al 9 found a significant advantage with the bipolar method, but no significant difference for bleeding tendency was shown in recent studies or in our patients. 10,23 An increased risk of stricture after bipolar resection 20,21 was not confirmed by our findings, which is in accordance with other authors. 8,10,14 The higher number of strictures in the 'bipolar' study arm of some authors 10 might be because of the TUR in saline system.…”
Section: Discussionsupporting
confidence: 88%
“…Literature by the manufacturer confirmed that the TUR in saline system did not meet the bipolar definition and the criteria set by the International Electrosurgical Commission, which requires both active and return electrodes to be attached to single support system. 24 Differences in the stricture rate found by other authors 20 were later reported to be statistically insignificant. 25 Our study is the largest comparison of two surgical approaches, with more than 2 years of follow-up so far (Table 6).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…6 Anecdotally, urologists have observed better intraoperative visibility during bipolar resection, which may also enhance resident education. 7 Bipolar TURP provides an equivalent relief of LUTS and QoL improvement at 6 months compared to conventional monopolar TURP. The safety profile of both procedures in regards to operative and postoperative complications was comparable.…”
Section: Discussionmentioning
confidence: 99%